Peran Madrasah Sebagai Rumah Kedua Dalam Membentuk Karakter dan Psikologi Anak Dengan Menerapkan Metode Pembelajaran Daring - Uci Dwi Cahya; Farahdiba Thahura (Insan Kreasi Media, 2022)
ABSTRACT COVID-19 pandemic has made major changes in the way of life, one of which is in the field of education. Teaching and learning process is carried out online (online). The independent character and psychology of students, the teacher must insert learning materials and also assignments with independent character values ​​and be able to create madrasah as second homes even with the atmosphere of learning from their respective homes. This community service provides training on how to create a madrasah that is comfortable for students and teachers must have knowledge of educational psychology because not all children have the same characteristics. The implementation is done online using an online application. It is hoped that this community service will be able to produce creative teachers in creating fun learning methods for students.